2021
DOI: 10.1080/21505594.2021.1922027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatitis E antigen kinetics and its diagnostic utility for prediction of the outcomes of hepatitis E virus genotype 1 infection

Abstract: HEV-Ag ELISA assay is a reliable diagnostic test in resource-limited areas. HEV genotype 1 (HEV-1) infections are either self-limited or progress to fulminant hepatic failure (FHF) and death if anti-HEV therapy is delayed. Limited data is available about the diagnostic utility of HEV Ag on HEV-1 infections. Herein wWe aimed to study the kinetics of HEV Ag during HEV-1 infections at different stages, i.e., acute HEV infection, recovery, and progression to FHF. Also, we evaluated the diagnostic utility of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Recent studies have shown that symptomatic HEV infections do occur in elderly people and those with pre-existing liver diseases. [ 50 , 51 , 52 ]. Seroprevalence studies have shown high occurrence of asymptomatic infections in the general population as well as pregnant women [ 53 , 54 ].…”
Section: Hepatitis Ementioning
confidence: 99%
“…Recent studies have shown that symptomatic HEV infections do occur in elderly people and those with pre-existing liver diseases. [ 50 , 51 , 52 ]. Seroprevalence studies have shown high occurrence of asymptomatic infections in the general population as well as pregnant women [ 53 , 54 ].…”
Section: Hepatitis Ementioning
confidence: 99%
“…Furthermore, veterinarians could be at risk for the development of chronic HEV infection [57][58][59]. Similarly, hematological malignancies, age, and a history of pre-existing liver diseases are considered as risk factors for the development of FHF caused by HEV gt1 [60,61]. In addition, HEV gt3 is linked to acute nontravelassociated hepatitis E, which can appear as fulminant hepatitis with encephalopathy and coagulation disorders [62].…”
Section: General Populationmentioning
confidence: 99%
“…Since HEV infection can exacerbate the course of hematologic diseases [ 147 ], adequate therapy is essential. Frequently, infections with the genotype HEV-1 lead to fatal courses, especially if the patients are of advanced age [ 175 , 176 ]. Reducing immunosuppression in hematologic patients is often difficult, which is why balanced administration of ribavirin is also an important pillar in this context [ 147 , 151 , 163 ].…”
Section: Clinical Link Between Lymphoid Cell Impairment and Hev Outcomementioning
confidence: 99%